Goal Setting and Performance Evaluation: An Attributional Analysis - Dossett, Dennis L.; Greenberg, Carl I. (Academy of Management Journal, 1981)
The present study considered the effect of goal setting on supervisors? evaluations of employees? performance and the causes attributed to that performance. Results indicated that attributional distortions were greater in the assigned than in the participative or self-set goal conditions. Supervisors rated the high participatively-set goal worker significantly higher in performance, ability, effort, and goal commitment than they rated the low participatively-set goal worker.